Stenting versus balloon dilatation in patients with tracheal benign stenosis: The STROBE trial. Issue 2 (23rd February 2022) - Marchioni, Alessandro; Andrisani, Dario; Tonelli, Roberto; Andreani, Alessandro; Cappiello, Gaia Francesca; Ori, Margherita; Gozzi, Filippo; Bruzzi, Giulia; Nani, Chiara; Feminò, Raimondo; Manicardi, Linda; Baroncini, Serena; et al.
Abstract: Background: It is well known that benign tracheal stenosis represents an obstacle to open surgery, and that its treatment could be challenging. Two endoscopic techniques have so far been adopted to restore tracheal patency: balloon dilatation (BA) through laryngoscopy, and tracheal stenting (ST) with rigid bronchoscopy. The main objective of this study was to compare the efficacy of BA and ST to treat benign tracheal stenosis not eligible for surgery. We also compared the rate of adverse events in the two treatment groups. Methods: A retrospective, observational cohort study was carried out at the University Hospital of Modena (Italy) from November 2012 to November 2017 in two separate departments. Patients were considered to be "stabilized" (primary outcome) if they did not report significant respiratory symptoms, or restenosis in the long‐term (2 years) following the endoscopic procedure. Results: Sixty‐six patients were included in the study (33 in the BA and 33 in the ST group, respectively). Unadjusted Kaplan–Meier estimates showed a greater therapeutic effect of ST compared to BA at 2 years (hazard ratio = 3.9 95%CI [1.5–9.8], p = .01). After adjusting for confounders, stratified analyses showed that this effect was significant in patients with complex stenosis, idiopathic etiology, and degree of stenosis >70%. Compared with BA, ST showed a higher rate of adverse events ( p = .01). Conclusions: Compared to BA, ST seems to be more effective in achieving stabilization of tracheal patency in complex benign tracheal stenosis, although burdened with a significantly higher number of adverse effects. These findings warrant future prospective study for confirmation. Level of evidence: 3. Abstract :